1994
DOI: 10.1002/hbm.460010303
|View full text |Cite
|
Sign up to set email alerts
|

Human brain atlas: For high‐resolution functional and anatomical mapping

Abstract: We present the new computerized Human Brain Atlas (HBA) for anatomical and functional mapping studies of the human brain. The HBA is based on many high-resolution magnetic resonance images of normal subjects and provides continuous updating of the mean shape and position of anatomical structures of the human brain. The structures are transformable by linear and nonlinear global and local transformations applied anywhere in 3-D pictures to fit the anatomical structures of individual brains, which, by reformatti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(139 citation statements)
references
References 27 publications
(37 reference statements)
1
138
0
Order By: Relevance
“…The mean location, its SD, and current orientation (blue dot, circle, and line, respectively) of the cuneus and inferior occipital sources are displayed in a standard brain (18). The red dot displays the mean location of left and right V1 from Hasnain et al (13), who reported, however, the average location of the upper and lower visual field representations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean location, its SD, and current orientation (blue dot, circle, and line, respectively) of the cuneus and inferior occipital sources are displayed in a standard brain (18). The red dot displays the mean location of left and right V1 from Hasnain et al (13), who reported, however, the average location of the upper and lower visual field representations.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of individual signals were calculated separately for each time point. For the group average, the individual estimates were aligned on a standard brain (18) and then averaged. The alignment phase applies first a 12-parameter affine transformation (11), followed by a refinement with an elastic nonlinear transformation (10).…”
Section: Methodsmentioning
confidence: 99%
“…The bilateral caudate nuclei were manually delineated on the structural MRI scans for each individual using Human Brain Atlas software (Roland et al, 1994). The cerebellum, where DA D1 receptor density is negligible, was delineated on six central slices and served as reference region (Hall et al, 1988).…”
Section: Pet Datamentioning
confidence: 99%
“…Recently, methods have been developed to generate probabilistic atlases of cortical areas in a stereotaxic coordinate system by matching the intensities of volumetric brain images via linear transformations (Talairach and Tournoux, 1988) or nonlinear transformations (Roland et al, 1994;Schormann and Zilles, 1998). These volume-based intersubject registration techniques were used to build a probabilistic atlas of human primary visual cortex (V1) (Amunts et al, 2000), as well as a number of other cortical areas (Amunts et al, 1999;Geyer et al, 1999;Grefkes et al, 2001;Morosan et al, 2001;Rademacher et al, 2001b,a;Eickhoff et al, 2007;Amunts et al, 2005;Wilms et al, 2005;Caspers et al, 2006).…”
Section: Introductionmentioning
confidence: 99%